Controlling H3+ Formation From Ethane Using Shaped Ultrafast Laser Pulses - Townsend, Tiana; Schwartz, Charles J.; Jochim, Bethany; P., Kanaka Raju; Severt, T.; Iwamoto, Naoki; Napierala, J. L.; Feizollah, Peyman; Tegegn, S. N.; Solomon, A.; Zhao, S.; Carnes, K. D.; et al. (Frontiers in Physics, 2021)
An adaptive learning algorithm coupled with 3D momentum-based feedback is used to identify intense laser pulse shapes that control H3+ formation from ethane. Specifically, we controlled the ratio of D2H+ to D3+ produced from the D3C-CH3 isotopologue of ethane, which selects between trihydrogen cations formed from atoms on one or both sides of ethane. We are able to modify the D2H+:D3+ ratio by a factor of up to three. In addition, two-dimensional scans of linear chirp and third-order dispersion are conducted for a few fourth-order dispersion values while the D2H+ and D3+ production rates are monitored. The optimized pulse is observed to influence the yield, kinetic energy release, and angular distribution of the D2H+ ions while the D3+ ion dynamics remain relatively stable. We subsequently conducted COLTRIMS experiments on C2D6 to complement the velocity map imaging data obtained during the control experiments and measured the branching ratio of two-body double ionization. Two-body D3+ + C2D3+ is the dominant final channel containing D3+ ions, although the three-body D + D3+ + C2D2+ final state is also observed.